The Role of the Asahan Resort Police Samapta Unit in Handling Misdemeanor Crimes through a Restorative Justice Approach - Hotlan Wanto Siahaan; Muhammad Arif Sahlepi; Rahmayanti Rahmayanti (Utan Kayu Publishing, 2025)
This study discusses the role of the Asahan Resort Police Samapta Unit in handling minor crimes through the application of a restorative justice approach. As one of the operational functions of the police, the Samapta Unit has the main task of maintaining public security and order, including rapid response to violations and misdemeanors. Through the restorative justice approach, Samapta seeks to resolve cases by prioritizing the restoration of relationships between perpetrators, victims, and the community, as well as minimizing lengthy judicial processes. The results of the discussion show that the role of Samapta includes preventive, responsive, and solutive actions through mediation, peace facilitation, and assistance in the peaceful case settlement process. The application of this approach is considered to be able to increase the effectiveness of case handling, reduce the burden of formal law enforcement, and strengthen public trust in the National Police. However, its success is still influenced by personnel commitment, supporting regulations, and active participation from related parties. This study emphasizes that the optimization of restorative justice by the Samapta Unit can be a strategic alternative in handling minor crimes that are more humane, fast, and just